The Effect of Carbon Performance, Foreign Ownership, and Firm Size on Carbon Emission Disclosure - Cahyaningsih Cahyaningsih; Deva Anggraeni Rahmadiah (AFRE (Accounting and Financial Review), 2024)
This study analyzes the effect of carbon performance, foreign ownership, and firm size on carbon emission disclosure. Based on the sample selection criteria, researchers analyzed 14 companies from the energy, raw goods, and primary consumer goods sectors listed on the Indonesia Stock Exchange for 2019-2021. The analytical method used is panel data regression analysis with a random effect model. The results of the study show that carbon performance positively affects on carbon emission disclosure. Companies with high carbon emissions tend to disclose more carbon emission items. Foreign ownership and firm size negatively affect carbon emission disclosure. Companies with fewer foreign investors and fewer assets disclose their carbon emissions to earn investors' trust and improve their access to sources of capital necessary for business growth and development.DOI: https://doi.org/10.26905/afr.v7i2.10923